Barron's how to prepare for the Toefl iBT : - Sharpe, Pamela J. (Trẻ, 2006)
The TOEFL (Test of English as a Foreign Language) is now being offered as an internet-based test, or iBT, and the new edition of Barron’s TOEFL manual has been completely revised and updated to reflect the new format. It presents seven full-length model TOEFL iBT tests with explanations or examples for all questions, including sample essays and speaking responses. The author also offers general orientation to the new TOEFL iBT, as well as a review of academic skills, which include note taking, paraphrasing, summarizing, and synthesizing. There is also a review of language skills—listening, speaking, reading, and writing.